Risk factors for Achilles tendinopathy in runners - an investigation of selected intrinsic, kinematic, kinetic and muscle activity factors that are associated with Achilles tendinopathy - Azevedo, Liane (MRC/UCT RU for Exercise and Sport Medicine, 2014)
The overarching purpose of this study was to investigate the multifactorial aetiology of Achilles tendinopathy. Variables such as training and injury history, lower limb alignment, running biomechanics and movement variability were investigated. This study also aims to understand how different sensory inputs, such as shoe or pain may affect biomechanics. Thirty four uninjured runners (UN) and twenty one runners with Achilles tendinopathy (AT) composed the population sample for this study. Questionnaire and lower limb measurements were used to investigate the multifactorial aetiology of the injury. Selected kinetic, kinematic and muscle activity parameters were employed to analyse the biomechanics aetiology of the injury. Runners performed 10 running trials at a self-selected speed in two running shoes with different hardness. Additionally, the UN runners ran for 10 min on the treadmill while the AT runners ran on the treadmill until they developed pain in the Achilles tendon. The results of the study showed that AT runners have a higher incidence of previous injury, run for more years, have reduced hamstring flexibility, and are heavier and taller than uninjured runners. The study also showed a reduced integrated electromyography activity (IEMG) of tibialis anterior and rectus femoris in the AT group during the running cycle. Stride to stride variability was similar between UN and AT runners but the biomechanics variability between participants were lower for the AT runners. No specific biomechanical adaptations were found between the two different shoe conditions (soft vs. hard). Similarly, biomechanics parameters were not altered at the onset of pain, but the reduced IEMG activity of tibialis anterior and rectus femoris were presented before and during the pain condition. It can, therefore, be concluded that runners with Achilles tendinopathy present reduced muscle activity during running which may be either a novel aetiological factor, or an adaptive response to the injury. The lower variability between runners with AT may indicate that these runners are less able to adjust their biomechanics according to their different functional behaviour or external input signals but this may require further investigation. Finally, it can also be concluded that the sensory inputs such as shoes and pain do not change this muscle activity pattern.